Effectiveness of the Implementation of Article 54 of Law Number 35 of 2009 concerning Narcotics on the Rehabilitation of Addicts and Victims of Narcotics Abuse - Kurniawan, Agus; RAS, Hernawati; Purnomo, Hadi (Civiliza Publishing, Indonesia., 2025)
Article 54 of Law No. 35 of 2009 concerning Narcotics, regarding drug rehabilitation, is an oppressive measure taken against drug addicts and victims of drug abuse. Police practices in Indonesia in making decisions with sanctions regarding the form of rehabilitation are very difficult and complex. The purpose of this study is to examine the effectiveness of the implementation of Article 54 of Law Number 35 of 2009 concerning Narcotics on the rehabilitation of drug addicts and victims of drug abuse. The research method used is the legal method and legal research specifications. Meanwhile, data analysis uses qualitative legal methods. The results of the study indicate that rehabilitation norms stipulated in Article 54 of the Republic of Indonesia Law No. 35 concerning drugs, according to questions about the circular letter from the Supreme Court (SEMA) No. 4 related to the placement of perpetrators of violence and victims of abuse in health and social organizations. Functional rehabilitation is higher than the penalty for imprisonment to reduce the number of finalists and increase the opportunity for social recovery for long-term drug addicts. Some positive effects of implementing Article 54: Increased ability to access rehabilitation and legal protection for drug addicts.